Socio-ecological Factors of Zoonotic Diseases Exposure in Colorado Dairy Workers. Issue 2 (3rd April 2021) - Palomares Velosa, Jairo Enrique; Salman, Mo D.; Roman-Muniz, Ivette N.; Reynolds, Stephen; Linke, Lyndsey; Magnuson, Roberta; McConnel, Craig S.; Rao, Sangeeta
ABSTRACT: Objectives : Zoonotic pathogens on dairy farms are a known risk for people who work and live there. Exposure and/or transmission of Salmonella serovars, E. coli (O157; H7), Campylobacter jejuni, and Cryptosporidium parvum have been documented to occur in the dairy farm environment. Social ecological factors have been identified as determinants of preventive behaviors of people at risk of infectious diseases. Methods : This study described the effect of socio-ecological factors on selected zoonotic bacterial and protozoal diseases in 42 workers of two dairy farms. Results : Occupational exposure to Salmonella ser. Dublin, E. coli, and Campylobacter spp . was confirmed. Self-efficacy and negative workplace perceptions were risk factors for Salmonella Dublin exposure (OR = 1.43[95% CI 1.11–2.22] & 1.22 [95% CI 1.02–1.53] respectively, ). Additionally, safety knowledge and risk perceptions were protective factors of exposure (OR = 0.90 [95% CI 0.79–1.00]). Positive perceptions of supervisors and coworkers was a protective factor of Campylobacter exposure (OR = 0.89 [95% CI 0.79–0.98]). Conclusion : Results indicated that the presence of a supporting organizational environment, good communication with supervisors and coworkers, and training on prevention of zoonotic diseases would potentially reduce occupational exposures to zoonotic diseases on these farms.